Barriers and Challenges Against the Utilization of Novel Teaching Methods for Nursing Students: Perspectives of Nursing Instructors - Mostafa Bijani; Zahra Moradi; Shahnaz Karimi; Zhila Fereidouni; Leila Nikrouz; Mahmood Hatami; Mohammad Mehdi Naghizadeh (Nurse Media: Journal of Nursing)
Background: The first step in effectively applying novel teaching methods is identifying barriers and challenges to implementing appropriate interventions. A literature review revealed no studies exploring nursing instructors’ viewpoints on the reasons for not using novel teaching methods.